Effectiveness of progesterone, cerclage and pessary for preventing preterm birth in singleton pregnancies: a systematic review and network meta‐analysis. (17th April 2017) - Jarde, A; Lutsiv, O; Park, CK; Beyene, J; Dodd, JM; Barrett, J; Shah, PS; Cook, JL; Saito, S; Biringer, AB; Sabatino, L; Giglia, L; et al.
Abstract : Background: Preterm birth (PTB) is the leading cause of infant death, but it is unclear which intervention is best to prevent it. Objectives: To compare progesterone, cerclage and pessary, determine their relative effects and rank them. Search strategy: We searched Medline, EMBASE, CINAHL, Cochrane CENTRAL and Web of Science (to April 2016), without restrictions, and screened references of previous reviews. Selection criteria: We included randomised trials of progesterone, cerclage or pessary for preventing PTB in women with singleton pregnancies at risk as defined by each study. Data collection and analysis: We extracted data by duplicate using a piloted form and performed Bayesian random‐effects network meta‐analyses and pairwise meta‐analyses. We rated evidence quality using GRADE, ranked interventions using SUCRA and calculated numbers needed to treat (NNT). Main results: We included 36 trials (9425 women; 25 low risk of bias trials). Progesterone ranked first or second for most outcomes, reducing PTB < 34 weeks [odds ratio (OR) 0.44; 95% credible interval (CrI) 0.22–0.79; NNT 9; low quality], <37 weeks (OR 0.58; 95% CrI 0.41–0.79; NNT 9; moderate quality), and neonatal death (OR 0.50; 95% CrI 0.28–0.85; NNT 35; high quality), compared with control, in women overall at risk. We found similar results in the subgroup with previous PTB, but only a reduction of PTB < 34 weeks in women with a short cervix. Pessary showed inconsistent benefit and cerclage did not reduce PTB < 37 or <34 weeks. Conclusions: Progesterone was the best intervention for preventing PTB in singleton pregnancies at risk, reducing PTB < 34 weeks, <37 weeks, neonatal demise and other sequelae. Tweetable abstract: Progesterone was better than cerclage and pessary to prevent preterm birth, neonatal death and more in network meta‐analysis. Tweetable abstract: Progesterone was better than cerclage and pessary to prevent preterm birth, neonatal death and more in network meta‐analysis.